Identification of the Types of Measured Acoustic Modes Inside the Operator’s Cab in a Bulldozer - DZIECHCIOWSKI, Zygmunt Szczepan; KOZIEŃ, Marek S. (Archives of Acoustics, 2014)
The aim of the study was to identify acoustic and structural modes in the spectrum obtained experimentally inside an operator’s cab in a bulldozer. Measurements were taken inside the operator’s cab in a caterpillar-track bulldozer Polremaco TD12NPH2E-2000, designed for work in underground mine enclosures. The acoustic pressure spectrum was obtained for varied rotational speeds of the engine during the free run of the machine. The reverberation time of the cab was determined basing on the pulse-type excited pressure response, followed by identification of the spectral components registered by measurements. Thus, identified frequencies were compared with natural acoustic frequencies registered inside the operator’s cab and with frequencies associated with the valves and ignition frequencies due to rotational speed and natural frequencies of structural vibrations of the cab’s walls. This study was conducted in an attempt to reduce the noise inside the operator’s cab using passive methods.